Combining tunable proteolytic sequences and a VEGF-mimetic peptide for the spatiotemporal control of angiogenesis within Elastin-Like Recombinamer scaffolds. (August 2021) - González-Pérez, Fernando; Ibáñez-Fonseca, Arturo; Alonso, Matilde; Rodríguez-Cabello, José Carlos
Abstract: One of the main challenges in regenerative medicine is the spatiotemporal control of angiogenesis, which is key for the successful repair of many tissues, and determines the proper integration of the implant through the generation of a functional vascular network. To this end, we have designed a three-dimensional (3D) model consisting of a coaxial binary elastin-like recombinamer (ELR) tubular construct. It displays fast and slow proteolytic hydrogels on its inner and outer part, respectively, both sensitive to the urokinase plasminogen activator protease. The ELRs used to build the scaffold included crosslinkable domains to stabilize the structure and a conjugated VEGF-derived peptide (QK) to induce angiogenesis. The mechanical and morphological evaluation of the ELR hydrogels proved their suitability for soft tissue regeneration. In addition, in vitro studies evidenced the effect of the QK peptide on endothelial cell spreading and anastomosis. Moreover, immunohistochemical analyses after subcutaneous implantation of the ELR hydrogels in mice showed the induction of a low macrophage response that resolved over time. The implantation of the 3D model constructs evidenced the ability of the fast proteolytic sequence and the QK peptide to guide cell infiltration and capillary formation in the pre-designed arrangement of the constructs. These results set the basis for the application of this type of scaffolds in regenerative medicine, where spatiotemporally controlled vascularization will help in the promotion of an optimal tissue repair. Statement of significance: Herein, we show the spatiotemporal control of angiogenesis in vivo by the combination of proteolytic sequences, with fast and slow degradation kinetics, and VEGF-mimetic peptide (QK) in a coaxial binary elastin-like recombinamer (ELR) tubular scaffold. These two bioactivities have been previously described for angiogenesis purposes, but have never been combined. This work demonstrates that the bioactivities act synergistically in promoting cell infiltration and subsequent vascularization, thus leading to a controlled evolution in space and time of the vascular microstructure within the hydrogel-like tubular scaffold. This effect has not been showed before and holds great potential for future vascular applications, which might be of great interest for a substantial part of Acta Biomaterialia readership. Graphical abstract: Image, graphical abstract